Why Do Investors Like Short-leg Securities? Evidence from a Textual Analysis of Buy Recommendations - Chen, Hailiang; Hwang, Byoung-Hyoun; Peng, Zhuozhen (Review of Financial Studies, 2025)
Abstract Our paper examines analyst reports and online stock opinion articles which recommend buying stocks that, based on the literature, trade at high prices and earn low future returns (“short-leg securities”). Using a textual analysis, we test whether the justifications primarily (1) emphasize safe-haven qualities, (2) indicate exuberance, or (3) highlight lottery-like features. Our results strongly point to (3). We subsequently validate our text-based inferences through a survey of institutional and retail investors with long positions in short-leg securities. Overall, perceived upside potential appears to play a material role in driving investor demand for stocks in the short legs of anomalies.